SEXUAL BEHAVIOR IN ADOLESCENT HIGH SCHOOL IN INDRAGIRI HILIR DISTRICT IN 2018 - Ernawati Ernawati; Mitra Mitra; Yessi Harnani; Nurhapipa Nurhapipa; Syamsul Bahri Rivai (JURNAL KESEHATAN MERCUSUAR, 2020)
Adolescent sexual behavior is all forms of behavior that are driven by sexual desire, a form of sexual behavior that is risky and is at low risk. The purpose of this study was to determine the sexual behavior of high school adolescents in Indragiri Hilir Regency in 2018, including risk factors, enabling and reinforcing. Cross sectional study design. Sample 233 people. The sampling procedure by systematic random sampling, data collection using questionnaires and data analysis was carried out univariately, bivariately by chi-square test and multivariate with multiple logistic regression tests. The results showed that the proportion of adolescents who carry out sexual behavior is at risk of 11.2%. Variables related to sexual behavior in adolescents are attitudes with p value 0.021 (POR: 3.441) and peers with p value 0.007 (POR: 3.906) and role family is a counfounding variable on attitudes and peers. It can be concluded that the bad influence of peers 4 times adolescents have a risky sexual behavior compared to the good influence of peers. It is expected that there should be school cooperation with the Education Agency in terms of providing counseling and including reproductive health education into the school curriculum, for parents and adolescents to be selective in choosing friends so that adolescents are not easily affected by the risk, especially in sexual matters.